Essays on poverty, inequality and education in India and Pakistan - Sarwar, Kafeel (2021)
In the first essay, entitled “A subnational analysis of poverty convergence: Evidence from India and Pakistan”, I analyze the subnational patterns of changes in poverty within the framework of poverty convergence. I also analyze the two distinct effects of poverty at the subnational level in India and Pakistan. In the second essay, entitled “A subnational analysis of inequality convergence: evidence from India and Pakistan,” I investigate whether the income inequalities are persistent overtime at the subnational level in India and Pakistan. In the third and last essay, entitled, “School grants and educational outcomes: The impact of the non-salary budget reform in Punjab-Pakistan, I study the effects of reform on education outcomes and achievements. I analyzed a decentralized school grant for public schools and address two questions. First, does the provision of a decentralized grant affect the school’s human capital and the school’s physical infrastructure? Second, does this decentralized grant improve education outcomes and achievements?
Keywords: Graue Literatur; Hochschulschrift